Predatory Journals Spamming for Publications: What Should Researchers Do? - Memon, Aamir Raoof (Science & Engineering Ethics, 2018)
In the internet era spam has become a big problem. Researchers are troubled with unsolicited or bulk spam emails inviting them to publish. However, this strategy has helped predatory journals hunt their prey and earn money. These journals have grown tremendously during the past few years despite serious efforts by researchers and scholarly organizations to hinder their growth. Predatory journals and publishers are often based in developing countries, and they potentially target researchers from these counties by using different tactics identified in previous research. In response to the spread of predatory publishing, scientists are trying to develop criteria and guidelines to help avoid them—for example, the recently reported “predatory rate”. This article attempts to (a) highlight the strategies used by predatory journals to convince researchers to publish with them, (b) report their article processing charges, (c) note their presence in Jeffrey Beall’s List of Predatory Publishers, (d) rank them based on the predatory rate, and (e) put forward suggestions for junior researchers (especially in developing counties), who are the most likely targets of predatory journals.